Canvassing the Challenges of the Literature Review for Master 1 Algerian EFL Learners - Rahmani, Mokhtaria; Mehdaoui, Djamila (LANGUAGE ART, 2023)
Writing an academic research paper at the end of master studies is a hallmark in students’ course of study as it testifies to their competency in research and academic writing. Yet, research is an arduous process, above all if the skills have not been internalized properly. Hindrances in conducting a literature review are glaring examples of research difficulties. Many studies have dwelt on those impediments, but no Algerian study has dwelt on this aspect. The present paper tries to canvass students’ weaknesses in writing an appropriate literature review. To realize that, a descriptive-analytical method, integrating qualitative and quantitative approaches, has been used. The sample population consists of the entire population of Master 1 EFL didactics students (31) at the University of Saida. Two research instruments have been selected for that purpose: a students’ questionnaire and an analysis of the learners’ homework pertaining to the literature reviews. The findings disclose that the major hindrances of the literature review are related, basically, to irrelevant content, coherence, non-use of original sources, and absence of transition markers which are due to poor reading skills, and disengagement of learners. The analysis puts into evidence the need for the consolidation of the reading skills that help to understand inferences and draw conclusions as to the strengths and weaknesses of scholars’ views.